N-alkylation of organo-imido substituted polyoxometalates: an efficient and stoichiometric approach for the easy post-modification of polyoxometalates1. Issue 10 (14th March 2015) - Khan, Rao Naumaan Nasim; Lv, Chunlin; Zhang, Jin; Hao, Jian; Wei, Yongge
<x xml:space="preserve">Abstract</x> A high-yield post-functionalization protocol developed here provides an easy inclusion of the desired organic groups on a POM's highly negative surface.